Infinity war : Trichomonas vaginalis and interactions with host immune response - Galego, Giulia Bongiorni (2023)
Trichomonas vaginalis is the pathological agent of human trichomoniasis. The incidence is 156 million cases worldwide. Due to the increasing resistance of isolates to approved drugs and clinical complications that include increased risk in the acquisition and transmission of HIV, cervical and prostate cancer, and adverse out-comes during pregnancy, increasing our understanding of the patho-gen’s interaction with the host immune response is essential. Produc-tion of cytokines and cells of innate immunity: Neutrophils and mac-rophages are the main cells involved in the fight against the parasite, while IL-8, IL-6 and TNF-α are the most produced cytokines in re-sponse to this infection. Clinical complications: T. vaginalis increases the acquisition of HIV, stimulates the invasiveness and growth of prostate cells, and generates an inflammatory environment that may lead to preterm birth. Endosymbiosis: Mycoplasma hominis increased cytotoxicity, growth, and survival rate of the parasite. Purinergic sig-naling: NTPD-ases and ecto-5’-nucleotidase helps in parasite survival by modulating the nucleotides levels in the microenvironment. Anti-bodies: IgG was detected in serum samples of rodents infected with isolates from symptomatic patients as well as patients with symp-toms. However, antibody production does not protect against a rein-fection. Vaccine candidate targets: The transient receptor potential- like channel of T. vaginalis (TvTRPV), cysteine peptidase, and α-actinin are currently cited as candidate targets for vaccine develop-ment. In this context, the understanding of mechanisms involved in the host-T. vaginalis interaction that elicit the immune response may contribute to the development of new targets to combat trichomoni-asis.